As representações sociais dos diretores das escolas estaduais da diretoria de ensino de Presidente Prudente - SP sobre o seu papel e sobre a escola pública - Azevedo, Patrícia Cralcev [UNESP] (2014)
This report, integrated with the research line Public Policy, Scholastic Organization and Tutors Education from the Postgraduate Program in Education of FCT-UNESP - Campus of Presidente Prudent-SP, aimed to analyze the social representation which the principals teachers of state schools of the Directorate of Education from Presidente Prudente have over the public schools and about their purpose. Thereby, the following questions sought to be answered: Who are the principals teachers of states schools of the Directorate of Education from Presidente Prudente? How these principals teachers understand their roles? What are the difficulties encountered in the conduct of their roles? This research had a qualitative approach and used as a methodological procedure the bibliographical and the documentary research. The development of this study was based on the theory of social representations of Serge Moscovici. The participants in this research were 35 school principals teachers. The data collected was based on a questionnaire involving word evocation, direct and indirect questions. For data analysis, the software's SPSS and EVOC were used, as well as the content analysis. Thorough the data analysis it is possible to perceive the school principals profile, to identify their social representations about the principal teacher, the public schools today, the today's student and about the today's teacher. The survey results verified that the school principal teacher is overwhelmed with responsibilities to be done inside the school and this professional does not have a positive social representation regarding the aspects that permeate the public school. It was also possible to list the major difficulties encountered in carrying out their functions as principals teachers, which have corroborate to the evoked social representations